Brachioplasty Refinements. Issue 4 (April 2020) - Rohrich, Rod J.; Mohan, Raja; Durand, Paul D.
Abstract : Summary: With a growing massive weight loss population, upper arm contouring continues to rise in popularity. Refinements in technique, such as modification of skin excision patterns and the adjunct use of liposuction, have allowed for safe and reproducible results. This article helps to understand the evolution of upper arm contouring and provides an update on the limited-incision medial brachioplasty. Details of preoperative markings and operative technique are clearly illustrated in the video included.